Gas Network Development in Compact Bentonite: Key Controls on the Stability of Flow Pathways. (20th May 2019) - Harrington, J. F.; Graham, C. C.; Cuss, R. J.; Norris, S.
Abstract : Compacted bentonite is proposed as an engineered barrier material within facilities for the geological disposal of radioactive waste. Barrier performance and its interaction with a free gas phase must be considered as part of sound repository design. This study involved the long-term experimental examination of gas flow in precompacted bentonite, with particular consideration of gas network stability. Results demonstrate that the stress field experienced by the clay is strongly coupled with gas flow. For the first time, three controls on this behaviour are considered: (i) injection flow rate, (ii) constant vs. variable gas pressure, and (iii) stimulation of the microfracture network. A detailed stress analysis is used to examine changes in the gas flow network. The results indicate a degree of metastability despite these changes, except in the case of stimulation of the microfracture network by removal of the primary drainage route. In this case, a rapid redevelopment of the gas flow network was observed. As such, availability of drainage pathways will represent a key control on the generation of peak gas pressures and distribution of gas within the engineered barrier. The cessation of gas flow is shown to result in crack closure and self-sealing. Observations from this study highlight that characterisation of the gas network distribution is of fundamental importance in predicting gas dissipation rates and understanding the long-term fate of gas in radioactive waste repositories.